Chemotherapeutic options in chronic lymphocytic leukemia: a meta-analysis of the randomized trials. CLL Trialists' Collaborative Group. - Richards, S (1999)
BACKGROUND: The randomized trials that evaluate the timing and intensity of initial chemotherapy for chronic lymphocytic leukemia (CLL) have, in general, been too small to provide separately reliable results. We compared the effects on survival of the following: a) immediate versus deferred chemotherapy for early-stage CLL and b) combination chemotherapy (e.g., cyclophosphamide and vincristine plus prednisone/prednisolone [COP] or COP plus doxorubicin [CHOP]) versus single-agent chlorambucil as first-line treatment for more advanced disease. METHODS: All relevant randomized trials, whether published or not, were sought for a collaborative meta-analysis involving centralized review of the data for each patient. RESULTS: There were 2048 patients with early disease in six trials of immediate versus deferred chemotherapy (chlorambucil or chlorambucil plus prednisone/prednisolone). The 10-year survival was slightly worse (but not statistically significantly so) with immediate chemotherapy (44% versus 47% survival; difference = -3%; 95% confidence interval [CI] = -10% to 4%). There were another 2022 patients in 10 trials of combination chemotherapy versus chlorambucil, with or without prednisone/prednisolone. The 5-year survival was 48 % in both cases (difference = 0%; 95% CI = -6% to 5%). A subgroup of six of these 10 trials involved an anthracycline-containing regimen but again overall survival appeared no better than with chlorambucil (anthracycline-based regimen: 325 deaths among 627 patients; chlorambucil: 306 deaths among 636 patients; death rate ratio = 1.07; 95% CI = 0.91-1.25; not statistically significant). CONCLUSIONS: In terms of survival, these trials support a conservative treatment strategy for CLL, i.e., no chemotherapy for most patients with early-stage disease, and single-agent chlorambucil as the first line of treatment for most patients with advanced disease, with no evidence of benefit from early inclusion of an anthracycline. This strategy will, however, need to be reconsidered as mature results become available from trials of other agents.